Intuitive Access to Smartphone Settings Using Relevance Model Trained by Contrastive Learning - Kim, Joonyoung; Lee, Kangwook; Shin, Haebin; Lee, Hurnjoo; Kang, Sechun; Choi, Byunguk; Shin, Dong; Lee, Joohyung (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
The more new features that are being added to smartphones, the harder it becomes for users to find them. This is because the feature names are usually short and there are just too many of them for the users to remember the exact words. The users are more comfortable asking contextual queries that describe the features they are looking for, but the standard term frequency-based search cannot process them. This paper presents a novel retrieval system for mobile features that accepts intuitive and contextual search queries. We trained a relevance model via contrastive learning from a pre-trained language model to perceive the contextual relevance between a query embedding and indexed mobile features. Also, to make it efficiently run on-device using minimal resources, we applied knowledge distillation to compress the model without degrading much performance. To verify the feasibility of our method, we collected test queries and conducted comparative experiments with the currently deployed search baselines. The results show that our system outperforms the others on contextual sentence queries and even on usual keyword-based queries.